Gugat Cerai pada Peradilan Agama bagi Muslimah yang Beralih Keyakinan Diluar Kehendaknya - Walangitan, Semuel (HUMANIORUM, 2024)
Divorce is something that no couple ever expects, but sometimes God's provisions cannot be changed by human will. In reality, to obtain legal certainty, so that the status of a marriage becomes clear, divorce must be based on a judicial decision that examines and decides on the divorce. It is interesting to know about efforts to file for divorce in the Religious Courts according to applicable law and the efforts that can be made by those who are no longer Muslim. This research is qualitative research with a normative juridical pattern which departs from a legal phenomenon that occurs in society and wants to know the answer immediately. Data collection involves the process of collecting information or/or data related to applicable norms, standards or rules. the authority of the Religious Courts which can only examine and decide cases of people who are Muslim. Those who change religion without their own will or because of encouragement and certain circumstances often still feel that they have an identity as a Muslim, so it is not uncommon for them to file a petition for divorce at the Religious Court and it is rejected because it is not within the authority of the Religious Court. The application for divorce should be filed in the general court or make efforts to restore personal identity that meets the requirements for filing with the Religious Courts.